482. Impact of COVID-19 Pandemic on Psychosocial and Clinical Factors among people with and without HIV living in Miami. (31st December 2020) - Uribe, Patricia RaccamarichClaudia S; Zetina, Ana S Salazar; Montgomerie, Emily K; Salguero, Douglas; Mantero, Alejandro M; Barreto, Irma S; Vazquez, Andres; Martinez, Paola; Morgan, Kristiana; Yanes, Nicolle L Rodriguez; Brophy, Theodora; Maddalon, Marissa; et al.
Abstract: Background: As the COronaVIrus Disease 2019 (COVID-19) continues to unfold, drastic changes in daily life pose significant challenges on mental and clinical health. While public health interventions such as national lockdowns and social distancing are enforced to reduce the spread of COVID-19, the psychosocial and physical consequences have yet to be determined that may disproportionately affect people living with HIV (PLWH). Methods: To evaluate the impact of COVID-related stress on mental and clinical health, we conducted a 20-minute questionnaire eliciting sociodemographic information, clinical and psychological factors from people living in Miami, Fl. All individuals >18 years with or without a history of COVID-19 were included. Participating PLWH were recruited from an existing HIV registry and HIV uninfected participants from community flyers and word of mouth. Results: A total of 135 participants were recruited from 05/2020-06/2020. The mean age was 50 years old, 73/135 (54%) were female, and 102/135 (75%) were PLWH. Among participating PLWH, 60/102 (58.8%) self-identified as African American, and 9/102 (8.8%) were positive for COVID-19 by a commercially approved test. Among HIV-negative participants, 15/33 (45.5%) self-identified as White and 11/33 (33%) were positive for COVID-19. Both PLWH and HIV-negative participants described significant disruptions in health care access (47%), difficulty paying basic needs (41%), and feelings of anxiety and depression (48%); there was no statistically significant difference by HIV status. However, HIV negative participants were less likely to experience job loss and income disruption compared to PLWH during the pandemic (70% for HIV-negative vs 48% for PLWH; OR 0.40, p=0.03). Conclusion: The impact of COVID-19 on emotional and clinical health is significant in both PLWH and HIV-negative groups. These findings highlight the need for providing mental and physical health care during the pandemic, especially for coping with stress and anxiety during these difficult times and ensuring adequate access to health care. Disclosures: All Authors : No reported disclosures